2020
DOI: 10.1088/1742-6596/1521/4/042040
|View full text |Cite
|
Sign up to set email alerts
|

The importance of science, technology, engineering, and mathematics (STEM) education to enhance students’ critical thinking skill in facing the industry 4.0

Abstract: The industry 4.0 marks the fast-growing technology in many fields in order to achieve process efficiency in all of aspect of the industries, including education. The efficiency is derived from a big data, a real-time dataset collected from a vast amount of data from many instruments. Big data processing is used to predict market trends, discover new problem-solving and many more. Critical thinking, statistics, computing and the ability to understand how the world works are among important factors that has to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 12 publications
0
37
0
4
Order By: Relevance
“…Based on the results of content validity (relevance) and construct validity (consistency) on the prototype of the CTC model test (see Table 3), it is seen that the CTC model's learning tools are valid and reliable (see Table 5). (Hafni et al, 2020). Moreover, the CTC model in this research was purposely developed to overcome problems that occur, namely low critical thinking disposition and skills of pre-service science teachers that was found in the preliminary study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of content validity (relevance) and construct validity (consistency) on the prototype of the CTC model test (see Table 3), it is seen that the CTC model's learning tools are valid and reliable (see Table 5). (Hafni et al, 2020). Moreover, the CTC model in this research was purposely developed to overcome problems that occur, namely low critical thinking disposition and skills of pre-service science teachers that was found in the preliminary study.…”
Section: Discussionmentioning
confidence: 99%
“…These rapid changes force individuals to make appropriate preparations and one of them is critical thinking skill. This skill is an important competency which allows individuals to face challenges and changes of the Industrial Revolution 4.0 preparedly (Ridho et al, 2021) (Ulger, 2018); (Hafni et al, 2020). However, in Indonesia, critical thinking is often neglected, especially in learning (Ali & Awan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…An example in this respect, with strict reference to Romania we find in [20]: "64% of large enterprises and 56% of SMEs that recruited ICT specialists during 2018, reported that vacancies for ICT specialists are hard to fill/. …in Romania at least 80% of enterprises that either recruited or tried to recruit ICT specialists reported such difficulties.‖ Another problem noted [21] by most teachers in STEM disciplines as well as in the automotive industry [19] is the lack of training in STEM area regarding the capacity of gathering the knowledgers for STEM profile that are at KET's understanding and using in order to create, design, innovate, and operated in a high tech environment, 75% of future jobs will involve STEM knowledge and skills [22, 23,24].…”
Section: Industry 40 Conceptsmentioning
confidence: 99%
“…El concepto de Industria 4.0, es muy conveniente, especialmente para las ciencias de la ingeniería básica, como la ingeniería informática, electrónica y de máquinas. Esto debe ser implementado como piloto en el currículo de ciencias [43]. Como resultado, el concepto de Industria 4.0, trae una innovación bastante significativa en términos tanto de la industria como de la universidad.…”
Section: Desafíos En La Educación En Ingenieríaunclassified